Monitoring Temperature and Heart Rate during Surgical Field Implantation of PTT-100 Satellite Transmitters in Greenland Sea Birds. (11th July 2011) - Sonne, Christian; Andersen, Steen; Mosbech, Anders; Flagstad, Annette; Merkel, Flemming
Abstract : Information on cloacae temperature (CT), heart rate (HR), Isoflurane use, and oxygen flow was collected during field implantation of Platform Terminal Transmitters (PTT-) 100 satellite transmitters in Greenland sea birds. Information was obtained from 14 intracoelomic and 5 subcutaneous implantations in thick-billed murres ( Uria lomvia ) and 9 intracoelomic implantations in common eiders ( Somateria mollissima ). CT decreased in the order subcutaneous murres > intracoelomic eiders > intracoelomic murres due to the explorative exposure to the surroundings and increased heat loss (murres smaller than eiders) and because the eider PTTs were preheated to 35 ∘ C. During all implantations, heat loss was prevented using electric heat and rescue blankets. Regarding HR, the fluctuations were most pronounced during the intracoelomic murre implantations as a result of lower PTT temperature and lower body size leading to more pronounced digital manipulations and stimulation of the pelvic nerve plexus. Based on these results, we therefore suggest that HR and CT are carefully monitored in order to adjust anaesthesia and recommend the use of an electric heat blanket and preheating of PTTs to body temperature in order to prevent unnecessary heat loss causing physiological stress to the birds.